Saudi Vision 2030: Upaya Nation Branding Arab Saudi via Saudi Pro League 2019-2023 - Akbar, Febrizky; Rasyidah, Resa (Global and Policy Journal of International Relations, 2024)
Saudi Arabia is heavily reliant on oil for its national income. This dependency led Prime Minister Mohammed bin Salman to launch Saudi Vision 2030 in 2016, aimed at transforming the country's economy. Saudi Vision 2030 is built on three pillars: a vibrant society, a thriving economy, and an ambitious nation. One key area identified to achieve this vision is sports, especially football, which is immensely popular in Saudi Arabia and worldwide. Saudi Arabia has its own local league, the Saudi Pro League. The Saudi government aims to enhance the country's nation branding through the Saudi Pro League, aligning with Saudi Vision 2030. The initiative started in 2019 with the "Our Tactics for Tomorrow" program, designed to develop football in Saudi Arabia. The turning point came in 2022 with the arrival of Cristiano Ronaldo, one of the greatest football players in history, which significantly raised the profile of the Saudi Pro League and attracted other star players. This influx of star players has boosted the fan base both domestically and internationally, indirectly enhancing Saudi Arabia's nation branding, which was previously not well-known for its football.Keywords: Saudi Arabia, Nation Branding, Saudi Vision 2030, Saudi Pro League.Arab Saudi merupakan negara yang sangat bergantung pada minyak dalam hal pendapatan negaranya. Hal tersebut membuat perdana menteri Arab Saudi, Mohammed bin Salman, mencetuskan gagasan Saudi Vision 2030 yang memiliki tujuan untuk mentransformasi perekonomian dari Kerajaan Arab Saudi pada tahun 2016. Dalam mencapai tujuan tersebut, Saudi Vision 2030 memiliki 3 pilar utama, yaitu vibrant society, thriving economy, dan ambitious nation. Dalam mencapai visi tersebut, salah satu bidang yang bisa diandalkan adalah melalui olahraga, yaitu sepak bola, yang merupakan olahraga terpopuler di Arab Saudi dan juga dunia. Arab Saudi sendiri memiliki liga lokalnya sendiri yang bernama Saudi Pro League. Melalui Saudi Pro League, pemerintah berusaha untuk meningkatkan nation branding Arab Saudi, sesuai dengan Saudi Vision 2030. Usaha pemerintah dalam meningkatkan nation branding Arab Saudi melalui Saudi Pro League dimulai pada tahun 2019, dimana pemerintah Kerajaan Arab Saudi memulai program yang disebut sebagai “Our Tactics for Tomorrow”. Program tersebut memiliki tujuan untuk mengembangkan sepak bola di Arab Saudi. Hingga akhirnya pada tahun 2022, kedatangan salah satu pemain sepak bola terbaik dalam sejarah, yaitu Cristiano Ronaldo, seketika membuat nama dari Saudi Pro League meningkat tajam dan membuat pemain-pemain bintang lainnya berdatangan ke liga tersebut. Kedatangan dari pemain-pemain bintang tersebut meningkatkan jumlah penggemar baik dalam negeri maupun luar negeri. Hal tersebut secara tidak langsung juga mempengaruhi nation branding dari Arab Saudi itu sendiri, yang sebelumnya tidak dikenal dengan sepak bolanya. Kata kunci: Arab Saudi, Nation Branding, Saudi Vision 2030, Saudi Pro League.DOI: https://doi.org/10.33005/jgp.v12i01.4303